Seasonal Variations in Groundwater Quality under Different Impacts Using Statistical Approaches - Giao Thanh Nguyen; Nhien Thi Hong Huynh (Salehan Institute of Higher Education, 2023)
The objective of this study was to evaluate seasonal fluctuations in groundwater quality, determine the effects of different stressors on this resource, and recognize the potential pollution sources in a coastal region of southern Vietnam. Eleven samples collected in Ben Tre province during the dry and wet seasons were then analyzed for sixteen parameters, including pH, total dissolved solids (TDS), salinity, total hardness (TH), ammonium (NH₄⁺-N), nitrite (NO₂ˉ-N), nitrate (NO₃ˉ-N), sulfate (SO₄²ˉ), chloride (Clˉ), iron (Fe), manganese (Mn), lead (Pb), mercury (Hg), arsenic (As), coliforms, and Escherichia coli (E. coli). Pearson correlation analysis, principal component analysis (PCA), and cluster analysis (CA) were employed. The results indicated that total dissolved solids, salinity, total hardness, Clˉ, E. coli and coliform were detected as contaminants in groundwater samples. The trend of fluctuations in the parameters was mostly higher in the dry season. Which Mn and coliform significantly fluctuated between the dry and wet seasons. Activities in industrial-craft areas, landfills and seawater-intruded areas negatively impacted groundwater quality, typically TDS in industrial-craft areas, coliform and E.coliat the landfill area. Six principal components obtained from PCA could explain 93.6% of the variance, and all parameters are responsible for variations in groundwater quality. Geology, discharged wastewater, landfill leachate, agricultural activities, and saltwater intrusion can be considered representative factors. CA grouped the collected samples into four clusters based on the similarity in water properties. The analysis results showed that the locations in each cluster have outstanding water quality characteristics, clusters I and III have high TDS characteristics, cluster II has coliforms, and cluster IV sets of locations with high salinity. This study is promised to partially fill the gap in comprehensive information on groundwater quality in the coastal province so that policymakers can develop sustainable water management strategies in the future. Doi: 10.28991/CEJ-2023-09-03-01 Full Text: PDF